EFFECT OF WATER EXTRACT OF PLANTS CONTAINING TANNIN ON IN VITRO METHAGONESIS AND FERMENTATION CHARACTERISTICS OF THE GRASS Pennisetum purpureophoides - Santoso, B.; Saragih, E.W.; Hariadi, B.Tj. (Diponegoro University, 2013)
This experiment was conducted to evaluate the effect of extract of plants containing tannin on invitro CH4 production, fermentation characteristics and nutrient degradability. Six of plant leaves i.e.Gliricidia sepium, Acacia mangium, Leucaena leucocephala, Desmodium intortum, Camellia sinensis,Calliandra calothyrsus and seed of Areca catechu were extracted by using water. Experimentaltreatments consisted of P. purpureophoides (300±5 mg) incubated alone or added with 1.2 mL of plantextracts. The in vitro neutral detergent fibre (NDF) degradability was determined using the first stagetechnique of Tilley and Terry. The results showed that total tannin concentration of plant extract rangedfrom 34 to 95 g/kg DM, and was lowest in D. intortum and highest in A. mangium. Methane productionwas significantly (P<0.001) lower with addition of A. mangium, L. leucocephala, A. catechu, C. sinensisand C. calothyrsus extracts compared to control. Total tannin had a close relationship with CH4production (r=-0.79). There was strong correlation between CH4 production and NDF degradability(r=0.61). It was concluded that water extracts of A. mangium, L. leucocephala, A. catechu, C. sinensisand C. calothyrsus have potential to be used as rumen manipulator in order to reduce CH4 production inruminants.